Job retention vocational rehabilitation for employed people with inflammatory arthritis (WORK-IA): a feasibility randomized controlled trial - Hammond, Alison; O’Brien, Rachel; Woodbridge, Sarah; Bradshaw, Lucy; Prior, Yeliz; Radford, Kathryn A.; Culley, June; Whitham, Diane; Pulikottil-Jacob, Ruth (Bio Med Central, 2017)
Background